Comparison of Four Serological Tests To Determine the CagA or VacA Status of Helicobacter pylori Strains - Yamaoka, Yoshio (American Society for Microbiology, 1998)
We compared four tests for antibodies to CagA or VacA, HelicoBlot 2.0, RIDA Blot Helicobacter, CHIRON RIBA H. pylori SIA, and an enzyme-linked immunosorbent assay using recombinant CagA. Immunoblot assays were accurate for determining Helicobacter pylori status but poor for determining CagA or VacA status (accuracy, 66 to 80% for CagA status and 34 to 67% for VacA status). None can be recommended for determining CagA or VacA status.